2020
DOI: 10.1111/ans.15757
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness and outcomes of carotid endarterectomy for symptomatic carotid artery stenosis: a single centre audit

Abstract: Background For patients presenting with symptomatic internal carotid artery stenosis, carotid endarterectomy (CEA) surgery is recommended to be performed generally within a 48‐hr to 14‐day window. This study aimed to assess timeliness of delivery, and outcomes, of CEA surgery in a tertiary vascular centre. Method Patients with symptomatic internal carotid artery stenosis who underwent CEA between 1 June 2014 and 31 June 2017 were identified and data were obtained from hospital records. The timeline of their jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Between 2005 and 2013, many vascular surgeons transitioned to performing most CEAs within 2 weeks of symptom onset, with the mean time to surgery decreasing from 25 to 6 days [ 25 ]. The median interval from index symptoms to revascularisation in our 50–99% SCS patients of 12.5 days is in keeping with recent international clinical practice guidelines which recommended that CEA be performed preferably within 2 weeks of symptom onset [ 2 6 , 25 28 ]. The median interval from MDM to revascularisation in patients with 50–99% SCS was 5.5 days, partly due to the fact that our vascular surgeons do not have routine access to ‘protected emergency theatre slots’ for patients warranting urgent carotid endarterectomy outside of their scheduled vascular surgery lists.…”
Section: Discussionsupporting
confidence: 83%
“…Between 2005 and 2013, many vascular surgeons transitioned to performing most CEAs within 2 weeks of symptom onset, with the mean time to surgery decreasing from 25 to 6 days [ 25 ]. The median interval from index symptoms to revascularisation in our 50–99% SCS patients of 12.5 days is in keeping with recent international clinical practice guidelines which recommended that CEA be performed preferably within 2 weeks of symptom onset [ 2 6 , 25 28 ]. The median interval from MDM to revascularisation in patients with 50–99% SCS was 5.5 days, partly due to the fact that our vascular surgeons do not have routine access to ‘protected emergency theatre slots’ for patients warranting urgent carotid endarterectomy outside of their scheduled vascular surgery lists.…”
Section: Discussionsupporting
confidence: 83%
“…Forty-seven studies, comprising 107 587 patients and 23 188 octogenarians, met the inclusion criteria: 7 prospective cohort studies, 25 retrospective cohort studies, 6 registries, and 7 randomized controlled trials. 1,6,7,12,18–58 Most of the cohorts were from North America (n=16), Europe (n=11), with 3 from Asia, 1 from Australia, and 1 from New Zealand. The year of publication, demographic details, study design, and surgical methods are summarized in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…13 CEA should be performed as soon as possible after stabilization of the neurological event. 13 Carotid stenting is risky in the earlier period of the neurological events. 9 In our multidisciplinary approach, we perform CEA as soon as possible; however, in patients with minimal brain infarct, we delay the procedure for 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…10 Currently, it was reported that the benefit of CEA is increases with earlier intervention. 13 CEA should be performed as soon as possible after stabilization of the neurological event. 13 Carotid stenting is risky in the earlier period of the neurological events.…”
Section: Discussionmentioning
confidence: 99%